2015
DOI: 10.3389/fpsyg.2015.01849
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Styles, Feeding Styles, Feeding Practices, and Weight Status in 4–12 Year-Old Children: A Systematic Review of the Literature

Abstract: Childhood is a critical period in the development of obesity. Eating patterns established early in life track into later life. Therefore, parental approaches to feeding in their general parenting style, feeding styles, and specific feeding practices will have a profound impact on how children eat and grow. A systematic research review following PRISMA guidelines was conducted to identify, discuss and integrate recent research investigating the relationship between parenting styles, feeding styles, feeding prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
455
6
26

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 479 publications
(543 citation statements)
references
References 90 publications
28
455
6
26
Order By: Relevance
“…Feeding practices that reflect coercive control, such as pressuring children to eat, restricting children's access and consumption of unhealthy foods, and using food to influence children's behaviors or regulate their emotions, appear especially detrimental to the development of healthy eating patterns and weight (Lansigan, Emond, & Gilbert-Diamond, 2015;Shloim, Edelson, Martin, & Hetherington, 2015;Vaughn et al, 2016;Ventura & Birch, 2008). Cross-sectional and experimental studies have established associations between these feeding practices and increased child preference for restricted foods, heightened responsiveness to the presence of palatable foods, and eating beyond satiety when restricted foods are made available (Galloway, Fiorito, Francis, & Birch, 2006;Jansen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Feeding practices that reflect coercive control, such as pressuring children to eat, restricting children's access and consumption of unhealthy foods, and using food to influence children's behaviors or regulate their emotions, appear especially detrimental to the development of healthy eating patterns and weight (Lansigan, Emond, & Gilbert-Diamond, 2015;Shloim, Edelson, Martin, & Hetherington, 2015;Vaughn et al, 2016;Ventura & Birch, 2008). Cross-sectional and experimental studies have established associations between these feeding practices and increased child preference for restricted foods, heightened responsiveness to the presence of palatable foods, and eating beyond satiety when restricted foods are made available (Galloway, Fiorito, Francis, & Birch, 2006;Jansen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The family has a determinant role during the learning process of the alimentation of the children, so that the life habits of the parents, the parenting styles and their interaction with the children are significant for the formation of the infant's eating habits. 5,12,20,21 In the analysis of food consumption, almost all children had main meals daily with the family at home. This finding is important considering that the family has a set of values, beliefs, knowledge and eating habits that may constitute a protective or risk factor for health.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in agreement with the international systematic review study that showed the relationship between parental style and child BMI. 20 This picture may be due to the current phenomenon of nutritional transition experienced in society, marked by the hypercaloric diet, monotonous, with foods with a high concentration of sugars, fats and salt. 27 In the domain "consumption of treats", it was observed that a relevant part of the parents of the children studied consume soft drinks and sweets daily.…”
Section: Discussionmentioning
confidence: 99%
“…3 the development of eating behaviors, attitudes towards eating and food preferences (Benton, 2004;Birch & Davison, 2001;Johnson, 2016;Peters, Sinn, Campell & Lynch, 2012;Shloim, Edelson, Martin & Hetherington, 2015;Steinsbekk, Belsky, & Wichstrøm, 2016;Syrad, Johnson, Wardle & Llewellyn, 2016) .…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%